Manually prepared lamellae for Descemet stripping endothelial keratoplasty (Pachy-DSEK): comparison of four dissection depths - Bertino,Pedro (2022)
ABSTRACT Purpose: This study aimed to compare four depths of manual dissection for the preparation of Descemet stripping endothelial keratoplasty lamellae. Methods: Eye bank corneas were randomized into four groups according to dissection depths: Pachy-100 (incision depth = central corneal thickness-safety margin of 100 µm), Pachy-50 (safety margin of 50 µm), Pachy-0 (no safety margin), and Pachy+50 (incision depth = central corneal thickness + 50 µm). All endothelial lamellae were prepared using a standardized method of manual dissection (Pachy-DSEK). The central, paracentral (3.0-mm zone), and peripheral (6.0-mm zone) lamella thicknesses and incision depths were measured by optical coherence tomography. The 3.0-mm and 6.0-mm zone central-to-peripheral thickness ratios were calculated. Results: Endothelial perforation occurred only in the Pachy+50 group (n=3, 30%). Central lamella’s thickness in Pachy-100, Pachy-50, Pachy-0, and Pachy+50 groups measured 185 ± 42 µm, 122 ± 29 µm, 114 ± 29 µm, and 58 ± 31 µm, respectively (p<0.001). The overall 3.0- and 6.0-mm C/P ratios were 0.97 ± 0.06 and 0.92 ± 0.14, respectively. Preoperative donor characteristics were not correlated with most thickness outcomes. The planned incision depth correlated significantly with most lamella’s thickness parameters (p<0.001). The overall thickness of the lamella negatively correlated with the planned incision depth (p<0.001, r=-0.580). The best outcome was found in the Pachy-0 group, as 75% of the lamellae measured <130 µm and there was no endothelial perforation. Conclusions: By using a standardized method of dissection, most manually prepared lamellae presented a planar shape. Setting the incision depth to the central corneal thickness did not result in endothelial perforation and a high percentage of ultrathin lamellae was achieved.